PENGARUH RASIO RESIRKULASI DAN KONSENTRASI COD INFLUEN TERHADAP KINERJA REAKTOR HIBRID AEROBIK - Eddy Soedjono (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2003)
Hybrid aerobic laboratory scale reactor study was aimed to examine the reactor performance at different recirculation ratios and COD feed. Four reactors were constructed and run in parallel with recirculation ratio of 0%, 25%, 50%, and 75%. Using a synthetic wastewater, COD feeds were 200 mg/l, 400 mg/l, and 600 mg/l. The reactors performance, in fact, was affected by the recirculation ratio and COD feed. Higher recirculation ratio caused a better COD and ammonia removal. On the other hand, the removal decreased when COD feeds were increased. Based on the soluble COD and BOD concentration, the COD, BOD, and ammonia removal at two hour hydraulic retention time were 60 – 78%, 80 – 90%, and 30 – 55% respectively. Although the ammonia removal was happened, nitrification was not identified.